Risk assessment for type 2 diabetes mellitus in the municipality of Golubac - Trifunović, Boban; Fišeković Kremić, Marina (General Practice, 2023)
Introduction. There are approximately 17.000 newcases of diabetes mellitus type 2 (DM2) in Serbia each year.A third of the newly diagnosed already has some late diseasecomplications and almost half of them are over 65.Objective. We aimed at determining the level and riskfactors for DM2 in respondents of different gender, age, andlifestyle in the Municipality of Golubac.Method. The study was conducted using the DM2questionnaire. The sample had 404 participants who werescreened in the Municipality of Golubac. Significant statisticalmethods were used in the study: frequency, t-test, ANOVAtest, and correlation analysis.Results. The study showed the majority of participants(40.1%) had slightly elevated risk for DM2, high risk wasfound in 14.9%, and very high risk in 3.2%. Moderate riskwas found in 27.5% of the participants and 14.4% had lowrisk. Women had a higher percentage of high and very highrisk for DM2 than men but no statistically significant differencewas found between men and women concerning the riskof developing the disease. With age, as well as obesity, therisk for DM2 increases. The participants who practiced regularphysical activity, as well as those who regularly consumedfruits and vegetables, had a lower risk for DM2.Conclusion. The study showed almost every fifth participanthad a high or very high risk for DM2, 81.7% wereoverweight, and 75% had previously diagnosed cardiovascularproblems. Registration of persons with an elevated risk forDM2 and further follow-up is a very important task for GPs(general practitioners).Keywords: diabetes, screening, risk factors, obesity
Keywords: diabetes; screening; risk factors; obesity